Modeling and Analysis of Energy/Exergy for Absorber Pipes of Linear Parabolic Concentrating Systems - Reza Alayi; Mahdi Mohkam; Hossein Monfared; Alibek Issakhov; Nima Khalilpoor (International Journal of Photoenergy)
In this paper, the physical parameters of the absorber pipe of a linear parabolic collector have been investigated. The types of solar collectors, specifically the linear parabolic collector, have been comprehensively studied. Then, the mathematical model of heat transfer in the absorber pipe of the collector has been presented based on valid references. Numerical solutions of the equations related to the absorber pipe were performed by MATLAB software, and the effects of the physical parameters of the absorber pipe on its efficiency were investigated. The results show that increasing the length of the absorber pipe causes a nonlinear decrease in the efficiency of the absorber pipe. One of the important results is the increase in fluid temperature due to the increase in the diameter of the adsorbent tube, which increases the diameter of the fluid temperature by 60 K, in which the parameter increases the efficiency by 0.38%.